Hybrid warfare under international law: is hybrid warfare a crime of aggression? - Hovalko, Kristīne (Riga Graduate School of Law, 2018)
The term hybrid warfare has been a subject to much of recent discussion regarding the current and future international political developments in the world. However, despite being widely used in the society, academia policy and military debates, there is no particular legal definition one could refer to, the legal aspects of the term of ‘hybrid warfare’ remain inadequately addressed and studied. The author of this thesis aims establish whether it is possible to amount hybrid warfare to the definition of the crime of aggression under the Rome Statute of the International Criminal Court and whether it is possible to prosecute hybrid warfare as crime of aggression. It also proposes alternative procedures of handling hybrid warfare, mainly with the concentration on the domain of Cyberspace and focusing on tackling certain elements hybrid warfare with the use of international law, as well as with the interpretation of suggested terms ‘force’, ‘attack’ and ‘weapon’. The author stresses out the importance of continuity and adaptability of international law in order to combat the rising threats of hybrid warfare.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Cyberspace; Hybrid warfare